KAJIAN PENGGUNAAN WADAH PENGEMASAN TERHADAP MUTU CABE RAWIT (Capsicum frutescens) YANG DISIMPAN PADA RUANG PENDINGIN - Diliyanti O. Kapoh; Frans Wenur; Douwes D. Malik; Stella M.E. Kairupan (Universitas Sam Ratulangi, 2016)
ABSTRACTThe objectives of the study were to measure the changes of water content, the weight losses, changes in color, texture and to determine the level of damage that occurs during storage chili pepper in a cold room and get the right kind of packaging to preserve the quality of chili pepper. The research uses descriptive method with three packaging treatments and three replications. The treatment consisted of (1) packing within bamboo baskets, (2) packaging in the nets sacks, and (3) packing within plastic bags, HDPE (high density polyethylene). The results showed that chili stored at cold temperatures (6-10 oC) using plastic bags deliver the lowest lost 1.37% after being stored for 20 days compared to the net bag packaging with the losses of 35.98% and packaging bamboo basket with a loss of 18.22%. Chili packed with plastic bag showed the water content of 57.8% higher than net bag packaging of 40.73% and a bamboo basket with a water content of 52.85%. The hardness value of the base was 0.00025 mm/g, the middle section of 9.89 m/g, and the end of 75.20 mm/g. The damage percentage of chili pepper stored by using bamboo basket packaging was 10.09%, and within the net bag packaging was 16.32% while packaging in the plastic bag was 8.13%.Keywords : Packaging, chili pepper, cold storage